THE EVALUATION OF NEWBORN PAIN CARRIED OUT BY THE NURSING TEAM - SILVA, LUANA MENDES (2018)
To analyze and describe the evaluation of the pain of the newborn performed by the nursing team and to highlight the main difficulties faced by the nurses. This is a literature review carried out by consulting the Virtual Health Library (VHL) database, supported by scientific productions published between 2010 and 2015. The inclusion criteria established were articles developed in Brazil, published in the Portuguese language, associated with the theme and the following descriptors: Pain, Newborn and nursing. 1020 articles were found according to the descriptors. After analysis according to the inclusion criteria, the selection of the articles was performed. 317 publications were from foreign languages. Of the remaining 703 publications, 669 articles do not fit within the inclusion criteria for the year of publication. Of the 34 that remained, only 14 have the theme about the evaluation of the pain of the NB performed by the nursing team. It is the responsibility of health professionals to seek strategies and use the best possible means for the reduction of pain not only in newborns, but also in patients in general.